Stability training and effectiveness of playing basketball - Worobel, M. (Central European Journal of Sport Sciences and Medicine, 2020)
The aim of this study is to review the available literature for factors affecting a basketball throw and the stabilization of the trunk. Searching for the most important elements which ought to be improved during training to increase the effectiveness of a throw and those which condition the correct stabilization of the trunk. The obtained results, after analyzing the literature, show that it is not possible to determine a single factor affecting a throw and the stabilization of the trunk. There are many factors that influence each other and, therefore, must be trained as one. There are biomechanical relationships between the effectiveness of making a throw, the positioning of the limbs, the trunk and the trajectory of the ball. It is important to mention the role of a factor outside biomechanics, such as the player`s psyche. Muscles have the greatest impact on stabilization. Muscle function would not be possible without proper control by the nervous system The conclusion section shows a large number of interacting factors responsible for the quality and effectiveness of the throw as well as for the stabilization of the trunk. This allows better planning and conducting of basketball training aimed at improving technique and throw effectiveness.